The state and public administration: have instruments of governance outrun governments? Introductory perspectives II. Issue 1 (2nd January 2016) - Milward, H. Brinton
Abstract : These introductory perspectives set the scene for this Special Issue (II) by echoing comments made in the introduction to Special Issue (I) in December 2015. Three critical questions are addressed: What is the role of the state in different countries with different histories and capabilities? Does it make a difference what the form of the state is and how well articulated the instruments of governance are in delivering effective public goods and services? Have instruments of governance outrun governments? The latter is the overall theme of the Special Issues. The three complement the questions which are posed at the outset of Special Issue (I) and stated again in this discussion.